Effectiveness and safety of DOACs for the prevention of recurrent VTE: a prospective cohort study. (14th October 2021) - Vinci, A; Vedovati, M C; De Natale, M G; Pierpaoli, L; Di Filippo, F; Agnelli, G; Becattini, C
Abstract: Background: In the direct oral anticoagulants (DOACs) era, extended anticoagulation after 6–12 months of treatment is an attractive strategy in patients with venous thromboembolism (VTE). Real-life data on the clinical benefit of DOAC over time is lacking. Purpose: The aim of this study is to assess the effectiveness and safety of DOACs in patients with acute VTE treated for variable periods. Methods: Data on patients with an objective diagnosis of acute VTE treated with DOACs were included in prospective cohort study. Study outcomes were recurrent VTE and major bleeding (ISTH definition). Results: Overall, 934 patients were included (mean age 67.0±16.0, male gender 51.4%). Three-hundred and forty-six patients had a deep vein thrombosis (37.0%), 98 (10.5%) had isolated pulmonary embolism and 490 (52.5%) had both. One-hundred and sixty-nine patients (18.1%) had an active cancer, 59 (6.3%) a history of cancer and 365 patients (39.1%) an unprovoked VTE. During DOAC treatment (mean 21.6 months), 7 recurrent VTEs and 25 major bleedings occurred. In 546 and in 98 patients, DOAC was continued with full and reduced doses, respectively. In 290 patients (43.8% unprovoked, 13.8% active cancer, 42.4% associated with non-cancer risk factor), anticoagulants were withdrawn (average treatment duration 8.8 months) and 22 recurrent VTEs occurred over a follow-up off-treatment period of 31.9 months. In these patients, 2 episodes of major bleeding were observed. Overall, 201 patients died; fatal PE occurred in 4 and fatal bleeding in 1 patient. Time course for recurrent VTE according to 2019 ESC risk for recurrence is reported in the Figure. Conclusions: In this cohort study, DOACs showed a good risk to benefit profile in the extended phase after an acute VTE event. FUNDunding Acknowledgement: Type of funding sources: None.